(untitled) (Bangladesh Journal of Pharmacology, 2016)
Psoriasis is a skin disorder characterized by skin inflammation and plaques. Induction of psoriasis in animal model include following steps: a) Selection of animal model, b) Hair removing from the back or ear, c) treatment of skin with Aldara, a cream containing 5% imiquimod and d) Observation. Imiquimod-induced skin inflammation in animal model resembles with psoriasis. Video Clip of Methodology: Psoriaisis-like skin: 9 min 10 sec Full Screen Alternate